2020
DOI: 10.1038/s42003-019-0734-6
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of 128 camels across Asia reveals origin and migration of domestic Bactrian camels

Abstract: The domestic Bactrian camels were treated as one of the principal means of locomotion between the eastern and western cultures in history. However, whether they originated from East Asia or Central Asia remains elusive. To address this question, we perform wholegenome sequencing of 128 camels across Asia. The extant wild and domestic Bactrian camels show remarkable genetic divergence, as they were split from dromedaries. The wild Bactrian camels also contribute little to the ancestry of domestic ones, although… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
429
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(459 citation statements)
references
References 49 publications
(61 reference statements)
27
429
3
Order By: Relevance
“…Similar to the principal components analysis, the results indicated that a small amount (6.0%) of C. dromedarius ancestry is present in a C. bactrianus individual, and larger amount of C. bactrianus ancestry in a C. ferus individual (16.6%). These values are markedly similar to values reported by Ming et al 23 , where C. dromedarius ancestry in C. bactrianus ranged between 1 and 10%, and C. bactrianus ancestry in three C. ferus individuals ranged between 7 and 15%. Introgression from the domestic species into both Mongolian and Chinese populations of the Critically Endangered wild camel has been reported elsewhere using mitochondrial DNA 29 , microsatellites 30 and the Y chromosome 31 , potentially jeopardizing the wild camel's genomic integrity and evolutionary independence (~1.1 million years) 14 .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to the principal components analysis, the results indicated that a small amount (6.0%) of C. dromedarius ancestry is present in a C. bactrianus individual, and larger amount of C. bactrianus ancestry in a C. ferus individual (16.6%). These values are markedly similar to values reported by Ming et al 23 , where C. dromedarius ancestry in C. bactrianus ranged between 1 and 10%, and C. bactrianus ancestry in three C. ferus individuals ranged between 7 and 15%. Introgression from the domestic species into both Mongolian and Chinese populations of the Critically Endangered wild camel has been reported elsewhere using mitochondrial DNA 29 , microsatellites 30 and the Y chromosome 31 , potentially jeopardizing the wild camel's genomic integrity and evolutionary independence (~1.1 million years) 14 .…”
Section: Resultssupporting
confidence: 90%
“…Within C. dromedarius sequences aligned to the intraspecific reference, both Ts/Tv (2.49) and the number of SNPs (2,818,163) were comparable with the interspecific alignment ( Table 1). The large number of SNPs shared between the domesticated species is consistent with known introgression events and has been observed in other genomic studies of camels 23 . Anthropogenic hybridization between the domesticated dromedary and Bactrian camel, especially in central Asia, is a widely practiced tradition of cross-breeding aimed at improving milk production (F1 backcrossed with dromedary), wool and meat yield, cold resistance (F1 backcrossed with Bactrian camel), or for camel wrestling 24,25 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…One possible explanation for these results is that the wild camel suffered strong population declines leading to the current status of "critically endangered" species (by the International Union for Conservation of Nature (IUCN)). Thus, with the number of individuals decreasing, loss of genetic diversity is unfortunately real [42,43]. Another possible explanation is that domestic Bactrian camels are under higher pathogenic pressure compared to the wild species.…”
Section: Nucleotide Diversity In Important Immune Gene Groupsmentioning
confidence: 99%
“…Thus, with the number of individuals decreasing, loss of genetic diversity is unfortunately real [34,35].…”
Section: Old World Camelids Genome Assemblies´ Improvementmentioning
confidence: 99%